1955
DOI: 10.1017/s0007485300030716
|View full text |Cite
|
Sign up to set email alerts
|

Mosquitos of the Maldive Islands

Abstract: A large collection of mosquitos made in five atolls of the Maldive Islands has revealed the presence of 15 species. These are listed and notes of taxonomic interest on seven of them are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1955
1955
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In the Maldives, the 20,000 existing wells represent the most important C. p. quinquefasciatus larval habitats (IYENGAR, 1952;VELIMIROVIC and CLARKE, 1975). In the Indian subcontinent, C. p. quinquefasciatus is present in rural areas where it develops in wells used for irrigation (YASUNO et al, 1975).…”
Section: Larvaementioning
confidence: 99%
“…In the Maldives, the 20,000 existing wells represent the most important C. p. quinquefasciatus larval habitats (IYENGAR, 1952;VELIMIROVIC and CLARKE, 1975). In the Indian subcontinent, C. p. quinquefasciatus is present in rural areas where it develops in wells used for irrigation (YASUNO et al, 1975).…”
Section: Larvaementioning
confidence: 99%
“…We also observed that females with chikungunya exhibited more arthritogenic symptoms compared with the males in our previous work. 14 Overall,24.4% of children were reportedly affected during the 2019 outbreak in the Maldives, and in our cohort, we observed 20% with confirmed infection, compared with 17% of children reportedly affected in an outbreak on the Indian subcontinent. 25,39 These data indicate that the approximate proportion of children affected during outbreaks is generally less than one-fourth of all cases.…”
Section: Discussionmentioning
confidence: 48%
“…[15][16][17][18][19][20][21][22][23] The Maldives, a tropical island archipelago in the Indian Ocean, experienced a CHIKV outbreak in 2005-2006 involving anthropophilic vector Aedes species mosquitos that inhabit these small coral islands. 24 The last major outbreak of CHIKV was reported in 2006 and involved 11,879 cases. Infection was confirmed in 67 of these cases and resulted in six fatalities.…”
Section: Introductionmentioning
confidence: 99%
“…MALDIVE AND LACCADIVE GROUPS. Iyengar (1952) listed 13 species from the Maldives. Two more species are added in a further paper by Iyengar & Menon (1955).…”
Section: Discussionmentioning
confidence: 99%
“…Iyengar (1952) listed 13 species from the Maldives. Two more species are added in a further paper by Iyengar & Menon (1955). * For information concerning mosquitos of the Mascarenes which has come to hand since this note was written see Halcrow (1954a, 6), Hamon (19536) and Mattingly & Bruce-Chwatt (1954).…”
Section: Discussionmentioning
confidence: 99%